Specific packaging and circulation of cytochromes P450, especially 2E1 isozyme, in human plasma exosomes and their implications in cellular communications - Kumar, Santosh (Biochem Biophys Res Commun, 2017)
Cytochrome P450 (CYP) enzymes metabolize the majority of xenobiotics and are mainly found in hepatic and some extra-hepatic cells. However, their presence and functional role in exosomes, small extracellular vesicles that are secreted from various cells into extracellular fluids including plasma, is unknown. In this study, we analyzed the expression and biological activity of CYP enzymes in human plasma exosomes. First, we optimized isolation of plasma exosomes and characterized them for their physical properties and quality. The results showed that the purity of exosomes (<200 nm) improved upon prior filtration of plasma using a 0.22 micron filter. We then analyzed the relative level of exosomal CYP mRNAs, proteins, and enzyme activity. The results showed that the relative level of CYP enzymes in exosomes is higher than in plasma, suggesting their specific packaging in exosomes. Of the seven CYP enzymes tested, the mRNA of CYP1B1, CYP2A6, CYP2E1, and CYP3A4 were detectable in exosomes. Interestingly, the relative level of CYP2E1 mRNA was >500-fold higher than the other CYPs. The results from the Western blot showed detectable levels of CYP1A1, CYP1B1, CYP2A6, CYP2E1, and CYP3A4. Our results also demonstrated that exosomal CYP2E1 and CYP3A4 show appreciable activity relative to their respective positive controls (CYP-induced baculosomes). Our results also showed that CYP2E1 is expressed relatively higher in plasma exosomes than hepatic and monocytic cells and exosomes derived from these cells. In conclusion, this is the first evidence of the specific packaging and circulation of CYP enzymes, especially CYP2E1, in human plasma exosomes. The findings have biological and clinical significance in terms of their implications in cellular communications and potential use of plasma exosomal CYPs as biomarkers.